Composition, distribution and diversity of tree species under different management systems in the hill forests of Bharse Village, Gulmi District, Western Nepal - Gautam, Chinta Mani; Watanabe, Teiji (Himalayan Journal of Sciences, 2007)
Species composition, distribution and diversity of tree species were compared in three forest stands in the Bharse area, Gulmi District, Nepal. These forests have distinct management systems and are used for different purposes: Raiker (RK) for controlled-cutting, Raniban (RB) for cattle grazing, and Thaple (TL) for both cutting and cattle grazing. The total density of trees in RK was higher (2640 ha-1) than that in RB (2533 ha-1) and TL (1875 ha-1). However, the largest basal area (105 m2ha-1) was found in RB while RK and TL were calculated at 72 m2ha-1 and 58 m2ha-1, respectively. The distribution of species showed clump behavior in the grazing forests whereas mixed (clump and regular) distribution occurred in the controlled-cutting forest. Trees with small diameter size were more in the controlled-cutting forest (RK) than the forests used for grazing and/or cutting (RB and TL). Species richness was highest in forest opened for cattle grazing. However, values of tree species diversity and evenness were higher in the controlled-cutting forest than in the forests with grazing and/ or cutting. One might conclude that controlled cutting is more effective than grazing and/or cutting in conserving the diversity of tree species. Key words: Trees, distribution, composition, diversity, management system, hill forest, Nepal Himalayan Journal of Sciences 3(5) 2005 p.67-74